2018
DOI: 10.1017/s0007114518002994
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid positional distribution (sn-2 fatty acids) and phospholipid composition in Chinese breast milk from colostrum to mature stage

Abstract: This study quantified the fatty acid profile with emphasis on the stereo-specifically numbered (sn) 2 positional distribution in TAG and the composition of main phospholipids at different lactation stages. Colostrum milk (n 70), transitional milk (n 96) and mature milk (n 82) were obtained longitudinally from healthy lactating women in Shanghai. During lactation, total fatty acid content increased, with SFA dominating in fatty acid profile. A high ratio of n-6:n-3 PUFA was observed as 11:1 over lactation due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 42 publications
4
22
1
2
Order By: Relevance
“…The fatty acid methyl ethers were then separated in a capillary column (Supelco 2560, 100 m × 0•25 mm × 0•20 μm; Sigma-Aldrich) and quantified by Agilent 7890B GC with flame ionisation detector (Agilent Tech.) (26) . The carrier gas was He with a flow rate of 0•8 ml/min and a split ratio of 1:20.…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…The fatty acid methyl ethers were then separated in a capillary column (Supelco 2560, 100 m × 0•25 mm × 0•20 μm; Sigma-Aldrich) and quantified by Agilent 7890B GC with flame ionisation detector (Agilent Tech.) (26) . The carrier gas was He with a flow rate of 0•8 ml/min and a split ratio of 1:20.…”
Section: Fatty Acid Analysismentioning
confidence: 99%
“…After birth, infants continue to obtain NA from human milk. Several publications have indicated that the NA concentration in human milk markedly decreases as lactation stages progress [10,11,12]. NA concentrations in colostrum (≤1 week postpartum) have been found to range from two- to six-fold higher than those in mature milk (>2 weeks and ≤16 weeks) [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Lingkar kepala bayi pada penelitian ini dikategorikan berdasarkan Kemenkes 25 dimana sebagian besar bayi (89,9%) memiliki ukuran lingkar kepala normal (Tabel 1). Rata-rata ukuran lingkar kepala bayi pada penelitian adalah 34,35 ± 1,41 cm yang tidak jauh berbeda dengan lingkar kepala bayi di Cina (34,5 ± 1 cm) 39 , India (34,5 ± 1,8 cm) 40 , dan Jepang (34,0 ± 2 cm) 41 .…”
Section: Hasil Dan Pembahasanunclassified